An integrative GIS approach to analyzing the impacts of septic systems on the coast of Florida, USA. (2nd September 2020) - Flanagan, Kyle; Dixon, Barnali; Rivenbark, Tess; Griffin, Dale
ABSTRACT: An estimated 2.7 million septic systems in Florida, USA are potential ground and surface water contaminant sources that may affect environmental and human health. This study examined the spatial distribution of septic systems, coastal surface water contamination, and related environmental factors of coastal Florida watersheds at the 8-digit hydrologic unit code level. Hydrology, in situ sampling data, and other ancillary data were combined in a geographic information system to examine spatial relationships. Spatial distribution data were correlated to nitrogen, Enterococci counts, and beach closures tabulated since 2000, 2007, and 2012. Significant positive correlations (α = 0.05) with nitrogen and Enterococci counts were consistent for percent agricultural cover, percent combined urban and agricultural cover, septic tank density, population density, and septic tank density in poorly drained soils. Beach closures since 2012 were significantly positively correlated (α = 0.05) to average impervious cover (IC) and percent urbanization. Statistics indicated that Enterococci counts, nitrogen, and beach closures may be related to specific environmental factors and septic tank densities. The combination of septic tanks in urban regions with high IC prone to elevated runoff could also be a factor in surface water contamination. Data availability was also highlighted as a limitation due to infrequent spatial and temporal sampling.